1999
DOI: 10.1007/s002470050591
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of increase in renal pelvic size on post-void sonography as a predictor of vesicoureteral reflux

Abstract: Increase in renal pelvic size on post-void ultrasound is not a reliable indicator of vesicoureteral reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…This prospective study has confirmed the hypothesis that fluctuation of the renal pelvis is associated with highgrade VUR, as others have suggested [9,10,11]. Highgrade VUR was persistent in those with fluctuation, necessitating surgery in the majority.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This prospective study has confirmed the hypothesis that fluctuation of the renal pelvis is associated with highgrade VUR, as others have suggested [9,10,11]. Highgrade VUR was persistent in those with fluctuation, necessitating surgery in the majority.…”
Section: Discussionsupporting
confidence: 88%
“…These sonographic signs include pelvic or ureteral wall thickening [2,6], calyceal or ureteral dilatation [2], pelvic dilatation [3,7], absence of corticomedullary differentiation [2,3], hyperechoic cortex or renal cysts [2,3], displacement of ureteric jet in the bladder [8], and intermittent dilatation and ballooning of the collecting system [9,10,11].…”
Section: Introductionmentioning
confidence: 98%
“…Eleven studies evaluated standard 119,139,175,176,183,185,186,210,212,214 or duplex 142 ultrasound compared with the reference standard of MCUG. One study 185 reported data for a variety of cut-off points.…”
Section: Conventional Ultrasoundmentioning
confidence: 99%
“…The renal size, however, was estimated by the examiners and not quantitatively recorded or compared to age-specific growth charts. Attempts have also been made to diagnose reflux by assessment of the diameter of the renal pelvis on US with a reported accuracy of over 90% [10,17], but these findings are limited by the small number of patients and have been disputed by a larger investigation [6].…”
Section: Discussionmentioning
confidence: 99%